DEVELOPMENT OF ZOLMITRIPTAN MOUTH DISSOLVING FILMS: FORMULATION VARIABLES, MECHANICAL PROPERTIES, AND IN VITRO DRUG RELEASE STUDIES - SUDHIR MADDELA; BUCHI N. NALLURI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present investigation is to prepare zolmitriptan (ZOL) mouth dissolving films (MDFs) and to investigate the influence of formulation variables on physicomechanical, chemical, and drug release properties of the prepared MDFs. Methods: The MDFs were prepared by solvent casting technique using wet film applicator. The impact of hydroxypropyl methylcellulose of different viscosity grades (hydroxy propyl methyl cellulose [HPMC] E3, E5, and E15), plasticizers (glycerol and polyethylene glycol [PEG]-400), and solubilizing agents (polyvinyl pyrrolidone [PVP K30] and sodium lauryl sulfate [SLS]) on physicomechanical, chemical, and drug release properties were evaluated. The MDFs were also characterized by Fourier-transform infrared spectroscopy, differential scanning calorimetry, and X-ray diffractometry studies. Results: The MDFs prepared were transparent and smooth and showed no recrystallization. The tensile strength of the MDFs increased significantly with an increase in polymer viscosities, and about a 2.63-fold increase in tensile strength was observed for HPMC E15 MDFs compared to E3, whereas an increase in film thickness resulted in brittle MDFs with low tensile strength. Similar results were observed with percent elongation and folding endurance of the MDFs. In vitro, drug release studies indicate that higher film thickness and polymer viscosities delayed the MDF disintegration and, in turn, the ZOL release. Addition of PVP K30 and SLS to HPMC E3 formulations resulted in 1.66- and 1.53-fold increase in ZOL release rates. Conclusion: Overall, F7 formulation showed quicker disintegration (within 11 s) and ZOL release rates (within 180 s) along with good physicomechanical properties. These results indicated that the disintegration and drug release of ZOL can be enhanced to a greater extent by optimizing formulation variables in MDFs.